AN ANALYSIS OF PARTICIPANTS’ ANXIETY IN SPEAKING AT EZPZ (ELEVATING ZENITHS OF PROFICIENCY AND ZEST) ENGLISH COMMUNITY - Manjani, Talin Fania; Jabu, Baso; Korompot, Chairil Anwar (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This study aims to explore participants’ anxiety in speaking at the EZPZ English Community. This study employed a qualitative descriptive method. The subjects consisted of 22 individuals, referred to as ‘participants,’ who participated in speaking sessions during FEZ activities. Data collection techniques included observation and interviews. The findings revealed two types of symptoms: psychological symptoms (nervousness, worry, difficulty concentrating, and blanking) and physiological symptoms (object touching, trembling, sweating, stammering, and avoiding eye contact). The participants experienced state anxiety and situation-specific anxiety. The contributing factors of anxiety were categorized into linguistic factors (lack of vocabulary, pronunciation, grammar, lack of fluency, and limited exposure to the target language) and non-linguistic factors (communication apprehension and fear of negative evaluation). To overcome anxiety, participants employed four common strategies: preparation, positive thinking, relaxation, and peer seeking, along with a newly uncovered strategy called 'calm retreat.' This study highlights that speaking anxiety is a critical concern not only in formal educational institutions but also in non-formal learning environments. Addressing this issue requires implementing suitable strategies that accommodate individual needs to help learners overcome the barriers preventing them from expressing their opinions.